Mechanism, Kinetics and Thermodynamics of Decomposition for High Energy Derivatives of [1,2,4]Triazolo[4,3-b][1,2,4,5]tetrazine - Aleksandr V. Stankevich; Svetlana G. Tolshchina; Anna V. Korotina; Gennady L. Rusinov; Irina V. Chemagina; Valery N. Charushin (Molecules, 2022)
This paper presents the data of research studies on the mechanisms, kinetics and thermodynamics of decomposition of three high-energy compounds: [1,2,4]triazolo[4,3-b][1,2,4,5]tetrazine-3,6-diamine (TTDA), 3-amino-6-hydrazino[1,2,4]triazolo[4,3-b][1,2,4,5]tetrazine (TTGA) and 3,6-dinitroamino[1,2,4]triazolo[4,3-b][1,2,4,5]tetrazine (DNTT). The points of change of the reaction mechanisms under thermal effects with different intensities from 0.1 to 2000 s−1 have been established. The values of activation and induction energies for the limiting stages of decomposition have been obtained. The formation of nanostructured carbon nitride (α-C3N4) in condensed decomposition products, cyanogen (C2N2) and hydrogen cyanide (HCN) in gaseous products have been shown. Concentration-energy diagrams for the reaction products have been compiled. The parameters of heat resistance and thermal safety proved to be: 349.5 °C and 358.2 °C for TTDA; 190.3 °C and 198.0 °C for TTGA; 113.4 °C and 114.1 °C for DNTT. The energy and thermodynamic properties have also been estimated. This work found the activation energy of the decomposition process to be 129.0 kJ/mol for TTDA, 212.2 kJ/mol for TTGA and 292.2 kJ/mol for DNTT. The average induction energy of the catalytic process (Ecat) for TTGA was established to be 21 kJ/mol, and for DNTT-1500–1700 kJ/mol. The induction energy of the inhibition process (Eing) of TTDA was estimated to be 800–1400 kJ/mol.